Laparoscopic cystectomy in pregnancy: an 8 year series - Ramli, Roszaman; Wan Ghazali, Hazim; Omar, Mohd Jamil; Zainuddin, Ahmad Murad (Japan International Cultural Exchange Foundation (JICEF), 2009)
Objective: To evaluate the maternal and fetal outcome of laparoscopic ovarian cystectomy in pregnancy Method: A cross sectional study with descriptive analysis of the retrospective data collected from the electronic medical records, of 249 women with ovarian cystectomy from January 2000 until June 2007. We then focused on 37 out of 41 pregnant cases who had laparoscopic cystectomy performed. Results: The mean age was 28.3 years old. The gestational age ranges from 5 weeks to 20 weeks. The mean gestation in which the surgery was performed was 14 weeks. The duration of surgery was 86.3 minutes and average blood loss was 170 mls. Only one case was converted to laparotomy. There were no visceral injuries in this series. There was no miscarriage, contractions or per vaginal bleeding post operatively. Two patients had wound infection and were treated as outpatient. One had preterm contraction at 28 weeks but the pregnancy progressed till term. The duration of hospital stay was 3.9 days. The average gestation age of delivery was 37.5 weeks and mean birth weight was 2.9 kg. There was no admission to the neonatal intensive care and the AS were 9/10. However there was 1 fresh still birth but it was due to abruptio placenta. The commonest tumours were mature teratoma, cystadenoma and endometrioma. Conclusion: Laparoscopic ovarian cystectomy in pregnant women is safe and feasible. However further randomized controlled trials with a large sample size should be performed.